Robot-as-a-Service: From Cloud to Peering Technologies - Kapitonov, Aleksandr; Lonshakov, Sergey; Bulatov, Vitaly; Montazam, Babak Kia; White, James (Frontiers in Robotics and AI, 2021)
This article is devoted to the historical overview of the Robot-as-a-Service concept. Several major scientific publications on the development of Robot-as-a-Service systems based on a service-oriented paradigm are considered. Much attention is paid to the analysis of a centralized approach in the development using cloud computing services and the search for the limitations of this approach. As a result, general conclusions on the reviewed publications are given, as well as the authors’ own vision of Robot-as-a-Service systems based on the concept of robot economics.